Performance measurement of a tracked vehicle system - Rahman, Mohammed Ataur; Mohiuddin, A. K. M.; Hossain, Altab (Springer New York LLC, 2011)
To improve crossing ability, the most important performance factor for tracked vehicle systems operating on low-bearing capacity peats, and to minimize income losses that result from downtime and maintenance costs, a vehicle was designed in order to adapt to operating condition changes. This article describes the mobile performance of a novel vehicle with segmented rubber tracks on a low-bearing capacity peat. At an equivalent travelling speed, the novel vehicle’s tractive performance in a variable operating environment caused by changes in terrain cohesiveness and hydrodynamic responses was superior to that of the previous model. The new vehicle, which could be operated on the Sepang peat, showed a tractive effort of 42.2% of the gross vehicle weight in field experiments; the recommended minimum tractive effort is between 30 and 36% of the gross vehicle weight.